2014
DOI: 10.1016/j.paid.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits, facets and cognitive performance: Age differences in their relations

Abstract: Personality traits and cognitive performance are related, but little work has examined how these associations vary by personality facet or age. 154 adults aged 22 to 84 completed the Brief Test of Adult Cognition by Telephone (BTACT) and the NEO Five Factor Personality Inventory. Hierarchical multiple regression analyses showed negative emotional aspects of personality (neuroticism, depression) were associated with lower reasoning, and social aspects of personality (assertiveness) were associated with faster r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 30 publications
11
55
0
1
Order By: Relevance
“…For instance, Passamonti et al () showed that openness/intellect positively predicted functional connectivity between midbrain regions (from which dopaminergic neurons project, such as substantia nigra and ventral tegmental area) and the dorsolateral prefrontal cortex, a critical area for WM, in line with findings that openness is associated with WM (DeYoung, Peterson, & Higgins, ; DeYoung, Shamosh, Green, Braver, & Gray, ). Moreover, DMN–openness associations may underlie the evidence that openness is positively linked to several cognitive abilities, regardless of age (e.g., memory, fluid and crystallized intelligence, verbal fluency), as observed in studies including young, middle‐aged, and older adults (Graham & Lachman, ; Soubelet & Salthouse, ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, Passamonti et al () showed that openness/intellect positively predicted functional connectivity between midbrain regions (from which dopaminergic neurons project, such as substantia nigra and ventral tegmental area) and the dorsolateral prefrontal cortex, a critical area for WM, in line with findings that openness is associated with WM (DeYoung, Peterson, & Higgins, ; DeYoung, Shamosh, Green, Braver, & Gray, ). Moreover, DMN–openness associations may underlie the evidence that openness is positively linked to several cognitive abilities, regardless of age (e.g., memory, fluid and crystallized intelligence, verbal fluency), as observed in studies including young, middle‐aged, and older adults (Graham & Lachman, ; Soubelet & Salthouse, ).…”
Section: Discussionmentioning
confidence: 90%
“…Resting‐state seed‐based studies have reported that agreeableness is positively associated with functional connectivity among some hubs of the DMN (Adelstein et al, ; Sampaio et al, ); however, there is no association between this trait and RSFC in studies using a whole‐brain approach (Dubois et al, ; Toschi et al, ). Likewise, there are several reports on the lack of association between agreeableness and regional brain volumes (Bjornebekk et al, ; Liu et al, ), and cognitive performance (Graham & Lachman, ; Soubelet & Salthouse, ). Our results reinforce the idea that aggressive behavior (e.g., lower agreeableness) is linked to brain networks relevant for cognitive/attention control (Wong et al, ), although more evidence is necessary to better understand this relationship.…”
Section: Discussionmentioning
confidence: 97%
“…Although this effect may seem minimal, recall that we measured global cognitive function using the Montreal Cognitive Assessment (MoCA). Neuroticism may have had an effect on specific cognitive domains such as perceptual speed, working and episodic memory, and fluid ability [39,58,59], and this effect may be worth further investigation because the magnitude of association between neuroticism and some specific cognitive domain may vary. Furthermore, it would be ideal to conduct a longitudinal analysis, trait neuroticism is found to be relatively stable [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be related to previous studies documenting a negative relationship between extraversion and some aspects of cognitive functioning (e.g., Graham & Lachman, 2014;Soubelet & Salthouse, 2011;Wolf & Ackerman, 2005).…”
Section: Correlates Of Apathy Symptom Factorssupporting
confidence: 82%